Protección al consumidor y propuesta Estatal en autorregulación privada y procedimientos administrativos: una aproximación inicial - Rejanovinschi Talledo, Moisés (2017)
Are State proposals on private self-regulation and administrative procedures on consumption adequate? The present papper analyzes the challenges of its application, providing a final reflection on the complaints in social networks.